2022
DOI: 10.1108/ijlm-11-2021-0522
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing supply chain information sharing with third party logistics service providers

Abstract: PurposeThis study evaluated the enhancement of information sharing practices with third party logistics service providers (3PLs) in a supply chain solutions company that provides transport and warehousing software in Johannesburg, South Africa.Design/methodology/approachA mixed methods case study was conducted to investigate the problem. Both strands of quantitative and qualitative data were given equal priority. Three rounds of primary data were sequentially collected, analysed and triangulated. An online que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…They found that e-sourcing is a direct determinant of supply chain agility regardless of the volatility of the environment because of the ability of e-sourcing to gather demand proposals and other relevant information through the system. The same result was found by other researchers, too (Valashiya 2019;Yang et al 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They found that e-sourcing is a direct determinant of supply chain agility regardless of the volatility of the environment because of the ability of e-sourcing to gather demand proposals and other relevant information through the system. The same result was found by other researchers, too (Valashiya 2019;Yang et al 2021).…”
Section: Discussionsupporting
confidence: 91%
“…However, although e-sourcing has more benefits in a volatile business environment, it has also suffered major drawbacks. Some technology-savvy suppliers may present an eyecatching show of their services online, which may not be essentially aligned with the actual product offerings (Valashiya 2019). That delays the entire supplier chain, as returns and replacement policies are affected.…”
Section: E-sourcing and Supply Chain Agility In A Volatile Business E...mentioning
confidence: 99%
“…For example, the geo-tagging system specifies how companies may use IoT programs to manage gas emission levels through supply chains [27]. Production technology reduces the consumption of manufacturing supplies and lowers the concentration of gas emissions, affecting corporate effectiveness [28]. Technology reduces gas emission levels and improves environmental performance.…”
Section: Supply Chain Resiliencementioning
confidence: 99%
“…2. Overall control structure (Valashiya & Luke, 2022) assets, reliability, and flexibility. Information sharing in the supply chain involves the satisfaction of information requirements of suppliers, customers, and inter-functional and intra-organizational participants.…”
Section: Supply Chain Componentsmentioning
confidence: 99%